2010
DOI: 10.1111/j.1601-0825.2009.01604.x
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes from human saliva as a source of microRNA biomarkers

Abstract: OBJECTIVE: The aim of this study was to examine the presence of microRNAs (miRNAs) within exosomes isolated from human saliva and to optimize and test methods for successful downstream applications. DESIGN: Exosomes isolated from fresh and frozen glandular and whole human saliva were used as a source of miRNAs. The presence of miRNAs was validated with TaqMan quantitative PCR and miRNA microarrays. RESULTS: We successfully isolated exosomes from human saliva from healthy controls and a patient with Sjö gren's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
439
1
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 647 publications
(466 citation statements)
references
References 23 publications
3
439
1
6
Order By: Relevance
“…Exosomes also contain ESCRT-II subunits able to specifically bind mRNA. It was also discovered the presence of microRNAs within exosomes isolated from fresh and frozen glandular and whole human saliva [54] Recently, exosomes from human saliva have been characterized for their mRNA content and 509 mRNA were found. In vitro, exosomes were able to transfer their genetic information to human oral keratinocytes modifying gene expression.…”
Section: Rna Contentmentioning
confidence: 99%
“…Exosomes also contain ESCRT-II subunits able to specifically bind mRNA. It was also discovered the presence of microRNAs within exosomes isolated from fresh and frozen glandular and whole human saliva [54] Recently, exosomes from human saliva have been characterized for their mRNA content and 509 mRNA were found. In vitro, exosomes were able to transfer their genetic information to human oral keratinocytes modifying gene expression.…”
Section: Rna Contentmentioning
confidence: 99%
“…Extracellular vesicles (EVs) are found in the extracellular space as well as in almost all body fluids, including blood [1], urine [2], saliva [3] and cerebrospinal fluid [4]. EVs carry and protect cargoes, including proteins, nucleic acids and lipids, from their cells of origin [5,6] (Figure 1(a)).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that placental-specific miRNAs, released via exosomes, can be exported from the placental trophoblast into the maternal circulation, where they can be found abundantly. MicroRNAs have been found within exosomes isolated from human saliva (Michael et al , 2010 ). These exosomes may transfer their genetic information to human oral keratinocytes, thus modifying gene expression in the cell.…”
Section: Nucleic Acidsmentioning
confidence: 99%